Pengaruh Parenting Style Dan Self-Esteem Terhadap Regulasi Emosi Pada Remaja Madya - Intan Fitria Wulandari; Asri Mutiara Putri; Vira Sandayanti (Nathiqiyyah, 2025)
Middle adolescence is a developmental stage characterized by emotional instability and identity exploration, requiring strong emotion regulation abilities. Emotion regulation refers to an individual’s ability to manage emotions from the moment they arise until they influence behavior. Environmental factors such as parenting style and internal factors like self-esteem are believed to play important roles in shaping this ability. Objective: This study aims to examine the influence of parenting style and self-esteem on emotion regulation in middle adolescents. Method: This research employed a quantitative approach using a survey method. A total of 212 students from SMA Negeri 16 Bandar Lampung were selected through a simple random sampling technique. The instruments used were the Emotion Regulation Questionnaire (ERQ), the Parenting Style and Dimensions Questionnaire–Short Version (PSDQ-SV), and the Coopersmith Self-Esteem Inventory (CSEI). The data were analyzed using two-way ANOVA analysis. Result: The results indicate that both parenting style and self-esteem significantly influence emotion regulation in middle adolescents. Moreover, an interaction effect was observed between parenting style and self-esteem in influencing emotional regulation. Conclusion: This study emphasizes the importance of implementing appropriate parenting styles and fostering positive self-esteem to enhance emotion regulation among middle adolescents.